Situating the Appeal of Fortnite Within Children's Changing Play Cultures. Issue 4 (June 2020) - Carter, Marcus; Moore, Kyle; Mavoa, Jane; Horst, Heather; gaspard, luke
Fortnite is a massively multiplayer online "battle royale" game that rapidly grew in 2018 to become one of the most popular digital games in the world, with a reported peak of 10.8 million concurrent players and 250 million registered players in March 2019. Based on 24 interviews with young people aged 9–14 (17 boys and 7 girls), this article sets out to provide an account of the appeal and experience of Fortnite . While it is impossible to pinpoint exactly why Fortnite has been such a phenomenal, global success, in this article, we argue that its appeal can be better explained by its intersections with YouTube and game livestreaming, the way the game acts as a vehicle for social capital and the performance of identity, and the rich sociality of play.